The Contribution of Zakat to Sustainable Financial Performance: Evidence from Sharia Compliance Firms - Agus Munandar (AFRE (Accounting and Financial Review), 2024)
Triple bottom line is mainly the focus of corporations to pursue a high reputation among stakeholders and to achieve high corporate financial performance (CFP). This paper seeks to investigate the correlation between zakat and sustainability of financial performance. This study employs a panel data regression model with Sharia compliant firms in Kuwait, Saudi Arabia, and Malaysia obtained from Thomson Reuters. This study reveals firms with strong zakat payments may not exhibit high levels of financial performance sustainability. This finding supports agency theory, which states that firms should creates financial benefit. Consistent with agency theory, shareholders perceive that zakat payment may not hold the same goals and principles as the shareholders. Thus, this relationship may not demonstrate positive relationship between zakat and sustainability financial. The findings of this paper contribute to Islamic and sustainability literature JEL Classification: G29, G30 DOI: https://doi.org/10.26905/afr.v7i3.13749